Peculiarities of Ag metallic nanoparticles formation in alkaline and alkaline-earth tetraborate glasses - Dutka, R.M.; Adamiv, V.T.; Burak, Ya.V.; Gamernyk, R.V.; Teslyuk, I.M. (Functional Materials, 2015)
Investigations of alkaline Li₂B₄O₇:Ag and alkaline-earth CaB₄O₇:Ag tetraborate glasses with Ag nanoparticles (Ag NPs) formed by thermal treatment in vacuum have been performed. It is ascertained that in volumes of the both glasses a small number of Ag NPs is formed, whereas their main mass is concentrated near the samples surface. It is obtained from the plasmon resonance results that, under the same annealing conditions, concentration of the Ag NPs in the near-surface layer of CaB₄O₇:Ag glass is appreciably smaller than in the near-surface layer of Li₂B₄O₇:Ag glass. This peculiarity is explained by difference between contributions of alkaline Li⁺ and alkaline-earth Ca²⁺ ions to processes of the Ag NPs formation in respective tetraborate glass. Remove selected